The strategic development of physiotherapy in South Africa paper 2: Mapping strategy - critical choices over 30 years - P. Bowerbank (AOSIS, 2001)
This paper demonstrates an unusual approach to trace decision makers' interpretations over time as they attempt to understand environmental events. The paper adopts an evolutionary perspective and methodologically, demonstrates a way of tracing changes in cause maps over time from available documents and statements. Arguments are offered for the usage of such data to infer cognitive processes. The South African Society of Physiotherapy is the subject of study.